Differential effects of HDAC inhibitors on PPN oscillatory activity in vivo. (15th March 2020) - Bisagno, Veronica; Bernardi, Maria Alejandra; Sanz Blasco, Sara; Urbano, Francisco J.; Garcia-Rill, Edgar
Abstract: The pedunculopontine nucleus (PPN) has long been known to be part of the reticular activating system (RAS) in charge of arousal and REM sleep. We previously showed that in vitro exposure to a HDAC Class I and II mixed inhibitor (TSA), or a specific HDAC class IIa inhibitor (MC 1568), decreased PPN gamma oscillations. Given the lack of information on systemic in vivo treatments on neuronal synaptic properties, the present study was designed to investigate the systemic effect of HDAC inhibitors (HDACi) on PPN rhythmicity. Rat pups were injected (acute, single dose) with TSA (4 or 20 mg/kg), MC1568 (4 or 20 mg/kg), or MS275 (20 or 100 mg/kg). Our results show that MC1568 (20 mg/kg) reduced mean frequency of PPN oscillations at gamma band, while increasing mean input resistance (Rm) of PPN neurons. For TSA (4 and 20 mg/kg), we observed reduced mean frequency of oscillations at gamma band and increased mean Rm of PPN neurons. Systemic administration of 20 mg/kg MC1568 and TSA effects on Rm were washed out after 60 min of in vitro incubation of PPN slices, suggesting an underlying functional recovery of PPN calcium-mediated gamma band oscillations over time. In addition, at a lower dose, 4 mg/kg, MC1568 and TSA induced higher mean amplitude gamma oscillations. Blocking HDAC class I might not have deleterious effects on gamma activity, but, more importantly, the inhibition of HDAC class I (at 100 mg/kg) increased gamma band oscillations. In conclusion, the present results in vivo validate our previous findings in vitro and further expand information on the effects of HDAC inhibition on PPN rhythmicity. PPN neurons require normal activity of HDAC class IIa in order to oscillate at gamma band. Graphical abstract: Red arrows represent statistical significant inhibition. Blue arrows represent statistical significant enhancement. ~ Represents absence of change.Our findings suggest that gamma oscillations in the PPN are finely tuned in vivo by the activity of HDAC class IIa. Sustained blocking of HDAC IIa blunted gamma band oscillations of PPN neurons. Blocking HDAC class I showed higher gamma band amplitudes. In conclusion, systemic administration of HDAC inhibitors might have either negative or positive effects on PPN rhythmicity depending of dose and group of HDAC affected. Image 105643 Highlights: HDAC class IIa inhibitors (acutely, i.p. ) blunted PPN oscillations at gamma band. HDAC class I inhibitors (100 mg/kg; i.p. ) increased PPN gamma band oscillations. We suggest the existence of a physiological HDAC class I/IIa balance in the PPN.